2022
DOI: 10.6018/sportk.550641
|View full text |Cite
|
Sign up to set email alerts
|

Efectividad de la suplementación nutricional con polifenoles sobre el daño muscular y marcadores de estrés oxidativo en diferentes tipos de ejercicios físicos: Una revisión de la literatura.

Abstract: During exercise, there is a redox imbalance that increases reactive oxygen species, generating oxidative stress that favors muscle damage, affecting physical and sports performance. Different antioxidant supplements have been used to optimize muscle recovery after physical exercise. However, the effects of various antioxidants have been counterproductive, since the reactive oxygen species generated by exercise are necessary for muscle adaptation and their reduction prevents correct intracellular signaling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Therefore, when antioxidant scavengers inhibit the PGC-1α/ Nrf2 pathway and reduce the levels and activity of antioxidant enzymes, such as SOD, CAT, GPX and mitochondrial biogenesis 17,[24][25][26]28 , physical exercise loses its preventive role against metabolic diseases linked to chronic OS when combined with antioxidant scavenger supplementation 24 . On the other hand, it has been demonstrated that indirect antioxidants, including polyunsaturated fatty acids 29 and certain polyphenols 3 , can induce a pre-conditioning effect similar to exercising. This effect enhances the content of antioxidant enzymes via the PGC-1α/Nrf2 pathway in metabolic diseases associated with OS 30 .…”
Section: Antioxidant Supplementation and Endogenousmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when antioxidant scavengers inhibit the PGC-1α/ Nrf2 pathway and reduce the levels and activity of antioxidant enzymes, such as SOD, CAT, GPX and mitochondrial biogenesis 17,[24][25][26]28 , physical exercise loses its preventive role against metabolic diseases linked to chronic OS when combined with antioxidant scavenger supplementation 24 . On the other hand, it has been demonstrated that indirect antioxidants, including polyunsaturated fatty acids 29 and certain polyphenols 3 , can induce a pre-conditioning effect similar to exercising. This effect enhances the content of antioxidant enzymes via the PGC-1α/Nrf2 pathway in metabolic diseases associated with OS 30 .…”
Section: Antioxidant Supplementation and Endogenousmentioning
confidence: 99%
“…Among the endogenous defense, some include endogenous antioxidants enzymes, such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX) 2 . In contrast, exogenous sources encompass ascorbic acid (Vit C), α-tocopherol (Vit E) and diverse polyphenols 3 .…”
Section: Introductionmentioning
confidence: 99%